Postmortem computed tomography and histopathology of distal limb lesions in giraffe (Giraffa spp.) under managed care - Liza Dadone; Steve Foxworth; Matthew S. Johnston; Sushan Han; Priya Bapodra-Villaverde; Erika Crook; Jill Erzar; John Griffioen; Kimberly L. Rainwater; Shirley LLizo; Joseph A. Smith; Kami Alvarado; et al. (PLoS ONE, 2026)
Foot structure and function are essential to the health and mobility of giraffe ( Giraffa spp.), yet comprehensive evaluations of distal limb pathology remain limited. This retrospective necropsy-based study used postmortem computed tomography (CT) of frozen distal limbs with targeted histopathology to characterize osseous and soft-tissue changes in a historical cohort of giraffe under managed care. Seventy-three distal limbs from 21 giraffe housed at 12 North American zoos (necropsies performed between 2004–2023) were evaluated. Lesions were graded on a scale of 0–3, and localized to either the medial or lateral digits. Findings were summarized at both the animal level (presence in ≥1 digit) and digit level. CT frequently identified multiple distal limb lesions within this necropsy cohort, including pedal osteitis, joint osteophytes, navicular apparatus changes, subchondral bone cyst-like lesions, laminar abnormalities, and flexor tendon mineralization. Navicular bone lesions were commonly identified, particularly in forelimbs, and frequently occurred in conjunction with abnormalities of the podotrochlear (navicular apparatus) region. These findings suggest that remodeling of the navicular bone and associated podotrochlear (navicular apparatus) structures may represent an important component of chronic distal limb disease and lameness in some affected giraffe. Laminar abnormalities consistent with chronic laminitis were common but were predominantly grade 1 on CT scoring, with grade 2 or 3 changes uncommon at both the digit and animal levels. Juvenile giraffe (<3 years) exhibited minimal CT-detectable orthopedic change, whereas lesions were more common and more extensive in older animals. Forelimbs more frequently exhibited navicular changes, and laminar abnormalities were more common in adult males than females. Distal phalanx fractures were identified in a subset of digits and occurred only in digits with pedal osteitis; fracture presence and severity were positively associated with greater pedal osteitis severity. Histopathology corroborated CT findings, demonstrating chronic laminar disruption, bone remodeling, and degenerative tendinopathy. Overall, these findings characterize historical patterns of distal limb pathology within a necropsy-based cohort of giraffe under managed care and provide context for continued refinement of preventive hoof-care strategies, husbandry practices, and early diagnostic monitoring aimed at promoting long-term orthopedic health.